Calcium carbonate-based permeable reactive barriers for iron and manganese groundwater remediation at landfills. (July 2016) - Wang, Yu; Pleasant, Saraya; Jain, Pradeep; Powell, Jon; Townsend, Timothy
Highlights: Pilot system built to remediate redox-impacted groundwater at a municipal landfill. Permeable reactive barriers (PRB) targeted iron and manganese removal. Limestone and crushed concrete PRB removed 95% and 91% of Fe and Mn in first year. Performance declined to 64% and 61% in the third year of operation, respectively. Results suggest effectiveness at smaller landfills, but limited at larger sites. Abstract: High concentrations of iron (Fe(II)) and manganese (Mn(II)) reductively dissolved from soil minerals have been detected in groundwater monitoring wells near many municipal solid waste landfills. Two in situ permeable reactive barriers (PRBs), comprised of limestone and crushed concrete, were installed downgradient of a closed, unlined landfill in Florida, USA, to remediate groundwater containing high concentrations of these metals. Influent groundwater to the PRBs contained mean Fe and Mn concentrations of approximately 30 mg/L and 1.62 mg/L, respectively. PRBs were constructed in the shallow aquifer (maximum depth 4.6 m below land surface) and groundwater was sampled from a network of nearby monitoring wells to evaluate barrier performance in removing these metals. PRBs significantly ( p < 0.05) removed dissolved Fe and Mn from influent groundwater; Fe was removed from influent water at average rates of 91% and 95% (by mass) for the limestone and crushed concrete PRBs, respectively, during the first year of the study. The performance of the PRBs declined after 3 years of operation, with Fe removal efficiency decreasing to 64% and 61% for limestone and concrete PRBs, respectively. A comparison of water quality in shallow and deep monitoring wells showed a more dramatic performance reduction in the deeper section of the concrete PRB, which was attributed to an influx of sediment into the barrier and settling of particulates from the upper portions of the PRBs. Although removal of Fe and Mn from redox impacts was achieved with the PRBs, the short time frame of effectiveness relative to the duration of a full-scale remediation effort may limit the applicability of these systems at some landfills because of the construction costs required.